ANALISIS MANAJEMEN OPERASIONAL DAN PENGENDALIAN KUALITAS PADA RANTAI PASOK INDUSTRI PENDUKUNG BLOK MASELA DI KEPULAUAN TANIMBAR - Sally Paulina Sandanafu (P3M Politeknik Negeri Ambon, 2026)
This study aims to evaluate the operational business model and quality control mechanisms within the supporting industries of the Masela Block project in the Tanimbar Islands. Using a qualitative descriptive approach, the research identifies critical success factors in operational management, specifically focusing on financial controlling and quality competitiveness. The results indicate that a robust integrated operational framework is essential to mitigate logistical risks and ensure that local MSMEs can meet international industrial standards. Keywords: Masela Block; Operational Management; Quality Control; Tanimbar Islands.